PERAN RESPON EMOSI DALAM MEMEDIASI PENGARUH KETIDAKPUASAN KONSUMEN TERHADAP PERPINDAHAN MEREK - Kadek Aria Satriawan; I Gusti Ayu Ketut Giantari (Forum Manajemen, 2017)
Purpose of this research is to explain the emotional response’s role in mediating the correlation between consumer dissatisfaction with brand switching to Teh Botol Sosro’s consumers to be Teh Pucuk Harum. This research was performed to consumers in Denpasar City by using questionnaire that was taken directly. Sample size used is 130 respondents with purposive sampling method. Data analysis technique used are path and sobel test. Research result shows that consumer dissatisfaction and emotional responses has significant and positive influence to the brand switching. The practice implication obtained from this research is that the Producer of Teh Botol Sosro should lessen the taste of jasmine aroma and add some sweet taste so it will implicate to the consumer’s satisfaction.